The Influence Of Corporate Social Entrepreneurship (CSE) Program And Mentoring On Community Competence Through Community Development As An Intervening Variable In The Baduga Community In The Sports Sector - Hilman, Ahmad Arief; Karunia, R Luki; Marwan, Jubery (Universitas Dharma Wacana, 2025)
This study investigates The Influence of corporate Social Entrepreneurship (CSE) Program And Mentoring on Community Competence Through Community Develeopment as an Intervening variable in The Baduga Community In The Sports Sector Indonesia. The concept of Corporate Social Entrepreneurship (CSE) has a role in encouraging the improvement of the economic welfare of the community, such as through the provision of competition programs and training in improving skills. In addition, it can encourage sustainable social innovation, increase community involvement and empowerment, accelerate social and infrastructure development and improve the reputation and sustainability of the company. The place of implementation of the research was carried out in the Baduga Sumedang Community environment, Sumedang Regency, West Java Province, which received the benefits of the Corporate Social Entrepreneurship (CSE) program of PT RPN. This research is classified into the type of explanatory research, namely research that intends to test and explain the relationship between independent variables (exogenous variables) and dependent variables (endogenous variables) (Sugiono, 2016). This study uses a hypothesis testing research design (Hypotheses Testing). This design was chosen because it will empirically test the influence between research variables. The sampling technique with the purposive sampling method was used to collect samples from the community. This method was chosen because it requires the determination of certain criteria for the sample to be targeted when distributing the research questionnaire (Taherdoost, 2016). The Isaac and Michael formula is used to determine the number of samples in purposive sampling with a tolerance of 10% error. This formula is used to calculate the number of samples needed. Based on the calculation of the Isaac and Michael formula mentioned above, the sample used for this study was 270 people who answered the questionnaire. Multiple regression analysis is used by researchers who intend to predict how the condition (rise and fall) of the dependent variable (criterion), where two or more independent variables as predictor factors are manipulated (increased or decreased in value). Multiple regression analysis is used by researchers who intend to predict the condition (up and down) of the dependent variable (criterium), where two or more independent variables are manipulated predictor factors (increasing and decreasing their values).